Does more money make you fat? The effects of quasi-experimental income transfers on adolescent and young adult obesity - Randall K. Q. Akee; Emilia Simeonova; William Copeland; Adrian Angold; E. Jane Costello (Institute for the Study of Labor (IZA), 2010)
This paper examines how exogenous income transfers during adolescence affect contemporaneous body mass index (BMI) measures and young adult obesity rates using evidence from the Great Smoky Mountains Study of Youth. The effects of extra income differ depending on the households' initial socio-economic status, tracing out an inverted U-shaped relationship between initial income and BMI. Youths who resided in families that had high pre-treatment annual incomes experience no change in young adult obesity rates as a result of the income transfers, while the BMI of poorer children increases. Part of this effect is due to differential increases in height, as well as weight. An exogenous annual transfer of 4,000 per adult family member results in an almost 4 cm gain in height-for-age. Adolescents coming from worse-off households experience an increase in weight only, without the corresponding change in height. The cumulative effects of the increase in household income persist for several years into young adulthood.
Keywords: I10; I12; I38; 330; obesity; health; cash transfer; adolescents; indigenous peoples